Hypothetical thinking and the winner's curse: An experimental investigation - Johannes Moser (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2017)
There is evidence that bidders fall prey to the winner's curse because they fail to extract information from hypothetical events - like winning an auction. This paper investigates experimentally whether bidders in a common value auction perform better when the requirements for this cognitive issue - also denoted by contingent reasoning - are relaxed, leaving all other parameters unchanged. The overall pattern of the data suggests that the problem of irrational over- and underbidding can be weakened by giving the subjects ex ante feedback about their bid, but unlike related studies I also find negative effects of additional information.
Keywords: D03; D44; D82; D83; C91; 330; Hypothetical thinking; cursed equilibrium; winner's curse